2014
DOI: 10.1111/jjns.12056
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among sexual self‐concept and sexual risk cognition toward sexual self‐efficacy in adolescents: Cause‐and‐effect model testing

Abstract: Based on social cognitive theory and a structural equation model technique, this study confirmed the mediating role of sexual risk cognition in the relationship between sexual self-concept and sexual self-efficacy. Also, sexual self-concept's direct and indirect effects explaining adolescents' sexual self-efficacy were found in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…The increased probability of sexual intercourse in relation to poor mental health among adolescents could be explained based on proposals made in several studies [11]. For instance, the concept of self-efficacy in Bandura's social cognitive theory suggests that people who are depressed have less capacity to take control over their lives, including areas pertaining to sexual behaviour [11,31]. Hence, adolescents who have higher sexual self-efficacy may exhibit less risky sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The increased probability of sexual intercourse in relation to poor mental health among adolescents could be explained based on proposals made in several studies [11]. For instance, the concept of self-efficacy in Bandura's social cognitive theory suggests that people who are depressed have less capacity to take control over their lives, including areas pertaining to sexual behaviour [11,31]. Hence, adolescents who have higher sexual self-efficacy may exhibit less risky sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Also, confidence in sexual relationships anticipates higher levels of SSE (39). Hsu et al (30) revealed the effect of sexual self concept on SSE. The results from their study supported that sexual self concept has a positive and direct effect on SSE and participants with higher sexual self concept and higher sexual risk cognition have higher SSE.…”
Section: Discussionmentioning
confidence: 99%
“…Deaf adolescents, like many others with various forms of disabilities, experience rejection, self-regret and depleted self-concept which are amplified by the challenges of how to cope and favourably compete with non-hearing impaired peers in a ‘world of words’. Based on the foregoing Bat-Chava (1993) , Hsu et al. (2015) and Van Gent et al.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies with considerable concerns for the self-concept of deaf adolescents have linked positive adjustment and lowered psychosocial challenges to positive self-concept, but the majority of such studies focused on the academic outcomes and communication, as well as social adjustment of deaf adolescents as the minority group in predominantly hearing communities ( Bat-Chava, 1993 ; Marschark and Hauser, 2008 ; Hintermair, 2008 ; Van Gent et al., 2011 ). Although there is not yet an established research study that has provided a link between self-concept and intimate image diffusion, especially among deaf adolescents, other studies ( Rostosky et al., 2008 ; Hsu et al., 2015 ; Jiannine, 2018 ) predominantly among non-deaf adolescents have shown that self-concept may influence risky sexual behaviour but not as it relates to sexting or intimate image diffusion via social networking sites. Studies have predominantly examined the impact of the components of 'self' (self-esteem, self-efficacy and self-concept) independently of each other on various forms of sexual behaviour among non-deaf adolescents, but little research exists on the same for the deaf who are members of a minority group in a predominantly hearing society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation